Social defragmentation and intergenerational transmission of educational inequalities on young people of Colombia - MIRANDA MORALES, JUAN CARLOS; Maldonado Pastor, Sergio; González Mejía, Xavier; Miranda Morales, Juan Carlos; Maldonado Pastor, Sergio; González Mejía, Xavier; MIRANDA MORALES, JUAN CARLOS; Maldonado Pastor, Sergio; González Mejía, Xavier (Corporación Universitaria Americana, 2023)
Introduction: This article is a partial product of the research project "Education and Equality" of the PROCARIBE Research group, within the framework of the line of research called Economics of Education, and addresses the problem of educational inequality in Colombia. This is one of the main challenges for the National Development Plan 2018- 2022, focused on peace, equity and education. Objective: Identify the challenges in terms of educational inequality that Colombia faces, especially among the young population and considering factors such as the intergenerational transmission of educational inequalities. Methodology: the article obeys a research carried out under the analytical empirical paradigm, a quantitative design and a type of explanatory research. The data were obtained from secondary information and collected by the National Department of Statistics, processed from the purification of the database and analyzed by using the Inequality Slope Index. Results: The general result indicates that the educational inequality gap between young people from different social strata has increased between 2011 and 2016, and that there is a positive correlation between the years of schooling of parents and their children, which validates the transmission hypothesis. intergenerational educational inequalities. In addition, it was possible to establish that young people who study in private institutions have a higher probability of completing ten years of schooling than those in official schools. Conclusion: In short, little progress has been made in terms of social defragmentation and better education can have a positive impact on future generations.